The Flexibility of the â€œFâ€ Word - Machmudah, Deinda Ratih (Universitas Negeri Semarang, 2021)
The â€œfâ€ word (fuck) cannot be separated from its taboo nature. This can reveal more deeply about its use which can be found every day that the â€œfâ€ word is not always used in negative terms and may be useful to enrich the knowledge about the characteristics of the â€œfâ€ word and to reduce the stigma about it that it has more than negative purpose in expressing emotions. This research would also clarify the reasons for the versatility of the â€œfâ€ word itself because of the kind that can be used to convey the sense of a specific emotional situation. This study was created because of the shortcomings that the previous study had; Horvat (2016), Jay and Janschewitz (2008), and Pluszczyk (2015) who have not studied the function of the â€œfâ€ word in detail. So the motivation is created with documentation technique and applying the framework of Shiedlower (1999) and Wang (2013) to further discuss that the â€œfâ€ word can be flexible in terms of word elements and their function in this study. The results have 6 different types of word element and 4 functions of â€œfâ€ word swearing